Targeted neonatal echocardiography and lung ultrasound in preterm infants with chronic lung disease with and without pulmonary hypertension, screened using a standardized algorithm - Sánchez-Becerra, Janneth Cristina; Guillén-Torres, Rogelio; Becerra-Becerra, Rosario; Márquez-González, Horacio; Ibarra-Ríos, Daniel (Frontiers in Pediatrics, 2023)
Introduction: Increased recognition of the development of chronic Pulmonary Hypertension (cPH) in preterm infants with Chronic Lung Disease (CLD) has prompted enhanced monitoring recognizing different phenotypes. Methods: All the newborns consulted for oxygen/respiratory support dependency (CLD assessment) from January 2018 to December 2021 were included. TnECHO and LUS were performed at 36 weeks postmenstrual age, screening for cPH-CLD. cPH related to increased pulmonary blood (cPH-IPBF) flow were referred to Pediatric Cardiology. The objective of the study was to identify cPH (cPH-CLD/IPBF) from all the CLD patients screened and to compare outcomes. Using a standardized algorithm, cPH-CLD patients, were treated with diuretics; before and after ultrasounds were analyzed. Results: 72 patients with CLD were screened. Twenty-two (30%) had cPH-CLD and nine (12%) had cPH-IPBF. cPH infants had more days of mechanical ventilation, retinopathy of prematurity and showed increased mortality. LUS pattern found in the 72 CLD patients consisted in a thickened pleural line and a B-Line interstitial heterogeneous pattern; 29%were found with consolidations. After diuretic therapy a step down in respiratory support occurred in 59% of cPH-CLD neonates. A decrease in respiratory rate (RR), right ventricular output (RVO), markers of pulmonary vascular resistance (PVR) and B-Line pattern was observed. In Tissue Doppler Imaging, biventricular diastolic function was modified after diuretics. Conclusions: cPH in CLD infants showed increased morbidity and mortality. In cPH-CLD patients after diuretic treatment a decrease in RR and step down in respiratory support was found. Follow-up ultrasound showed a decrease in RVO, markers of PVR and B-Lines. .